Mixed Diffusion-Jump Process Modeling of Exchange Rate Movements - Akgiray, Vedat; Booth, G. Geoffrey (The Review of Economics and Statistics, 1988)
This study demonstrates that the mixed diffusion-jump process is superior to the stable laws or a mixture of normals as a model of exchange rate changes for the British pound, French franc, and the We st German mark relative to the United States dollar. The parameter value s for the mixed diffusion-jump process are dependent on the monetary policy regime in force in the United States, with the estimates for the franc and mark being intertemporally similar but different from the pound. Copyright 1988 by MIT Press.